Composite flame-retardant cable material and preparation method thereof
By forming a barrier protective layer on the inner substrate surface of the cable material and promoting cross-linking reaction at high temperatures, the problem of flame retardant separation and mechanical properties of cable material at high temperatures is solved, higher flame retardancy and mechanical properties are achieved, and the service life of the cable is extended.
Patent Information
- Application Number
- CN202411973455.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-30
AI Technical Summary
Existing cable materials are prone to separation between flame retardants and polymers at high temperatures, and adding high-level flame retardants will reduce the processing performance and mechanical strength of the cable materials, and cannot take into account both flame retardant and processing performance.
By using an inorganic material modified suspension and silane coupling agent to form a barrier protective layer on the inner substrate surface of LDPE, HPCTP and PBPP, combined with DCP and TAIC to promote LDPE cross-linking at high temperature, and further activate the cross-linking reaction through heat treatment to form a stable three-dimensional network structure.
It improves the flame retardancy and mechanical properties of the cable material, optimizes the three-dimensional mesh structure, extends the service life of the cable, and enhances the thermal stability and long-term weather resistance of the material.
Smart Images

Figure CN119694682A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cables, and in particular to a composite flame-retardant cable material and a preparation method thereof. Background Art
[0002] Cable materials are widely used in modern industry and communications, and their performance is directly related to the safety and reliability of cables. In order to meet the flame retardant requirements in high temperature environments, conventional cable materials are usually filled with flame retardants to improve their flame retardant properties. However, when flame retardants are used to improve the flame retardancy of cable materials, there is a poor bonding between flame retardants and polymers, which are prone to separation under high temperatures or other extreme environments, affecting the service life of the cable. Although filling with high content of flame retardants can improve the flame retardant properties, it will significantly reduce the processing performance and mechanical strength of the cable materials, and it is impossible to achieve both flame retardancy and processing performance. Summary of the invention
[0003] The purpose of the present invention is to provide a composite flame-retardant cable material and a preparation method thereof, so as to solve the problems that the flame retardant and the polymer in the existing cable material separate at high temperature and the addition of the flame retardant significantly reduces the processing performance and mechanical strength of the cable material.
[0004] To achieve this object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing a composite flame-retardant cable material, the preparation method comprising: S1: obtaining a modified suspension according to an inorganic material and a silane coupling agent, wherein the inorganic material comprises one or more of expanded graphite, montmorillonite, and magnesium hydroxide; S2: at a preset temperature, LDPE, HPCTP and PBPP are melt-blended to form a uniformly dispersed inner layer matrix; S3: uniformly dispersing the modified suspension on the surface of the inner layer substrate by coating to form a barrier protective layer to obtain a composite substrate; S4: mixing the composite matrix with DCP and TAIC, cross-linking and extruding at high temperature to form a composite flame retardant material; S5: Extruding the composite flame-retardant material and cooling it to form it, and then heat-treating the extruded material to obtain a composite flame-retardant cable material.
[0005] Preferably, the step S1: obtaining a modified suspension according to an inorganic material and a silane coupling agent, wherein the inorganic material comprises one or more of expanded graphite, montmorillonite, and magnesium hydroxide, comprises: S11: adding the inorganic material into the anhydrous ethanol solution at a mass ratio of 1:10 and stirring and dispersing the inorganic material; during the dispersing process, ultrasonic vibration is used to assist the dispersion to obtain an inorganic suspension; S12: weighing a silane coupling agent according to 5% to 8% of the mass of the inorganic material and preparing an activation solution, adjusting the pH value of the activation solution, and stirring to obtain an activated coupling agent solution; S13: slowly adding the modified suspension into the activated coupling agent solution, and continuously stirring for 2 hours to obtain a modified suspension, wherein the suspended matter in the modified suspension is a modified inorganic substance.
[0006] Preferably, the step of melt blending LDPE, HPCTP and PBPP at a preset temperature to form a uniformly dispersed inner layer matrix comprises: S21: dry-mix 15% to 25% HPCTP and 5% to 10% PBPP powder to obtain a uniformly distributed flame retardant powder; S22: adding 60% to 70% LDPE into the extruder, and controlling the LDPE particles to melt into a viscous state according to preset conditions; S23: adjusting the temperature in the extruder, and adding the flame retardant powder into the extruder in multiple times; S24: Adjust the speed and maintain the temperature, perform high shear mixing on the mixture, and then extrude the inner layer matrix.
[0007] Preferably, when the modified inorganic substance needs to be stored for a long time, S2 further includes S14: vacuum filtering, separating, washing, and drying the modified suspension to obtain the modified inorganic substance; The S3 includes S30: preparing an ethanol-water mixed solution to obtain the modified inorganic substance, and slowly adding the modified inorganic substance into the ethanol-water mixed solution to obtain the modified suspension.
[0008] Preferably, the modified inorganic substance accounts for 8% to 12% of the composite matrix.
[0009] Preferably, the step S4: mixing the composite matrix with DCP and TAIC, and subjecting the composite matrix to high temperature extrusion and cross-linking reaction at 170° C. to 190° C. to form a composite flame retardant material comprises: S41: obtaining DCP and TAIC, dissolving the DCP and TAIC in a small amount of anhydrous ethanol, and stirring to form a uniform cross-linking spray liquid; S42: spraying the cross-linking spray liquid uniformly onto the composite matrix through a spraying device, and controlling the composite matrix to mix and rotate; S43: drying the composite matrix, DCP and TAIC that have been mixed together, and adding the dried mixture into a twin-screw extruder; S44: performing segmented processing on the mixture entering the twin-screw extruder to complete crosslinking and then extrude to obtain a molten material, wherein the segmented processing sequentially includes: feeding processing, melting processing, mixing processing, and homogenizing processing; S45: Extruding the molten material to obtain a composite flame retardant material.
[0010] Preferably, the step S5: extruding the composite flame retardant material, cooling it to form it, and then heat treating the extruded material to obtain the composite flame retardant cable material comprises: S51: Cooling the composite flame retardant material by combining water cooling and air cooling, and screening qualified composite flame retardant materials; S52: performing hot air drying on the composite flame retardant material, first adjusting the temperature step by step to increase the activation of the cross-linking reaction; S53: Cooling the composite flame-retardant material that has undergone cross-linking reaction again to obtain the composite flame-retardant cable material.
[0011] Preferably, the preparation method further comprises: S6: uniformly dispersing the modified suspension on the surface of the composite flame-retardant cable material by coating to form a protective layer.
[0012] In a second aspect, the present invention provides a composite flame-retardant cable material, which is prepared according to the preparation method provided in the first aspect, and the ratio of raw materials of the composite flame-retardant cable material includes: Low-density polyethylene (LDPE): 60% to 70%; Hexaphenoxycyclotriphosphazene (HPCTP): 15% to 25%; Phenoxypolyphosphazene (PBPP): 5% to 10%; Dicumyl peroxide (DCP): 1.2% to 2%; Triallyl isocyanurate (TAIC): 0.3% to 0.5%; Modified suspension; The modified suspension comprises: Inorganic materials: 8% to 12%, wherein the inorganic materials include: one or more of expanded graphite, montmorillonite, and magnesium hydroxide; Ethanol: 60%-70%; Water: 10%-20%; Silane coupling agent: 5%~8%; Glacial acetic acid: trace amount (about 0.5%).
[0013] Preferably, the inorganic material comprises: expanded graphite, montmorillonite and magnesium hydroxide, and the mass ratio thereof is 4:3:3.
[0014] Compared with the prior art, the present invention has the following beneficial effects: a barrier protective film is formed on the surface of an inner layer substrate produced by melt blending LDPE, HPCTP and PBPP using an inorganic material to form a composite substrate, and then DCP and TAIC are used to promote cross-linking of LDPE at high temperature before extrusion, and the extruded composite flame-retardant material is heat-treated to obtain a composite flame-retardant cable material, and during the heat treatment, LDPE is controlled to be further cross-linked, the cross-linking degree of the material is increased, the three-dimensional network structure is optimized, and the flame retardancy and mechanical properties of the cable material are improved.
[0015] The surface of the inorganic material is modified by a silane coupling agent, which enhances the compatibility of the inorganic material with the matrix material and improves the interfacial bonding force of the barrier protective layer. Before cross-linking, LDPE, HPCTP and PBPP are melt-blended to make each component evenly dispersed, avoid local enrichment, and improve the flame retardant uniformity of the material. The inorganic material is coated on the inner layer matrix to form a complete barrier protective layer, which effectively prevents the migration of HPCTP under high temperature conditions and improves the long-term flame retardant performance of the material. DCP and TAIC are used to ensure uniform cross-linking reaction and improve the cross-linking degree of the composite material. At the same time, under the cross-linking reaction conditions, it can ensure that the inorganic material will not melt and its performance will not be affected, maintain the integrity and interlayer structure of the inner and outer layer materials, and avoid interface damage or performance degradation during high-temperature extrusion. Finally, the extruded composite flame retardant material is heat-treated to further activate the residual cross-linking reaction, form a stable three-dimensional cross-linking structure, and improve the flame retardant performance and thermal stability of the material. At the same time, the heat treatment releases the residual stress inside the composite flame retardant material, improves the dimensional stability and long-term weather resistance, and extends the service life of the cable. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0017] The structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with this technology. They are not used to limit the conditions under which the present invention can be implemented, and therefore have no substantive technical significance. Any structural modification, change in proportion or adjustment of size, without affecting the effects and purposes that can be achieved by the present invention, should still fall within the scope of the technical contents disclosed by the present invention.
[0018] Figure 1 A schematic flow chart of the method for preparing the composite flame-retardant cable material provided in Example 1; DETAILED DESCRIPTION In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] In the description of the present invention, it should be understood that the terms "upper", "lower", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation of the present invention. It should be noted that when a component is considered to be "connected" to another component, it may be directly connected to the other component or there may be a centrally arranged component at the same time.
[0020] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.
[0021] Example 1 Please refer to Figure 1 The embodiment of the present invention provides a method for preparing a composite flame-retardant cable material, the preparation method comprising: S1: obtaining a modified suspension according to an inorganic material and a silane coupling agent, wherein the inorganic material comprises one or more of expanded graphite, montmorillonite and magnesium hydroxide.
[0022] Specifically, the ethanol solution uses anhydrous ethanol solution, which is a polar solvent and helps to reduce the van der Waals force on the surface of the flaky inorganic material, so that the flaky layer is fully dispersed; the silane coupling agent is a compound whose molecule contains a siloxy group (such as Si-OH) and an organic functional group, such as γ-aminopropyltriethoxysilane (KH550) and methyltriethoxysilane (MTES). Through the surface modification of the silane coupling agent, the hydrophilic surface of the inorganic material is converted into hydrophobicity, thereby improving its dispersibility and interfacial bonding force in the organic matrix (LDPE).
[0023] The S1 includes: S11: adding the inorganic material to the anhydrous ethanol solution at a mass ratio of 1:10 and stirring to disperse the inorganic material, and performing ultrasonic oscillation to assist the dispersion during the dispersion process to obtain an inorganic suspension.
[0024] Add inorganic material water into anhydrous ethanol solution and stir and disperse for 30 minutes to allow the surface of the inorganic material to adsorb the liquid to break the surface agglomeration state; during the dispersion process, ultrasonic oscillation (frequency 20kHz, power 200W) is used to assist dispersion. By combining ultrasonic oscillation with the action of anhydrous ethanol solvent, the initial dispersion of the inorganic material is improved to the nanoscale, further improving the uniformity of the inorganic flakes and avoiding agglomeration.
[0025] S12: Weighing a silane coupling agent according to 5% to 8% of the mass of the inorganic material and preparing an activation solution, adjusting the pH value of the activation solution, and stirring to obtain an activated coupling agent solution.
[0026] Pour anhydrous ethanol into a reaction container with a stirrer, obtain silane coupling agent according to 5% to 8% of the mass of the inorganic material and add it dropwise into the anhydrous ethanol, control the stirring speed at 200 to 300 rpm, and stir until the silane coupling agent is completely dissolved; after stirring evenly, add a small amount of deionized water and stir at room temperature for 10 to 15 minutes to fully hydrolyze the coupling agent to obtain an activated coupling agent solution.
[0027] Determination of the amount of anhydrous ethanol and deionized water: First, obtain the amount of anhydrous ethanol according to 5 times the mass of the coupling agent, obtain the amount of deionized water according to 2 times the mass of the coupling agent, and then adjust the volume ratio of anhydrous ethanol: deionized water to 9:1-8:2. First, obtain the mass of anhydrous ethanol and the mass of deionized water according to the mass of the coupling agent, determine the amount of solvent based on the mass of the coupling agent, ensure that the amount of solvent matches the reaction requirements of the coupling agent, and avoid waste or insufficiency; convert the mass of anhydrous ethanol and deionized water into the volume of the solvent, and determine whether the converted volume ratio of anhydrous ethanol: deionized water is within 9:1-8:2. If not, adjust the volume of the solvent to make its volume ratio within 9:1-8:2, and adjust the ratio of anhydrous ethanol to deionized water to the range to ensure the reaction rate and hydrolysis effect.
[0028] The pH value of the activation solution is adjusted by glacial acetic acid, and the temperature is controlled at 30°C~40°C and stirred for 10~20 minutes to obtain an activated coupling agent solution. By adding a small amount of deionized water and adjusting the pH value to pH 3~5 with glacial acetic acid, the premature self-condensation reaction of the silane coupling agent can be inhibited, so that the silanol remains chemically active in the solution. At the same time, a small amount of water can balance the rate and efficiency of the hydrolysis reaction of the silane coupling agent in the solution, so that the activation solution can generate uniform silanol under stable conditions (a small amount of water can induce partial hydrolysis of the siloxy group to form an intermediate active group Si-OH).
[0029] S13: slowly adding the modified suspension into the activated coupling agent solution and continuously stirring for 2 hours to obtain a modified suspension.
[0030] Slow addition can ensure that the activated coupling agent solution is in uniform contact with the inorganic material suspension, avoiding excessive local reaction of the coupling agent, thereby making the reaction more uniform. Preferably, the addition speed is controlled to 1 mL / min.
[0031] At a temperature of 30-40°C, the stirring speed was set to 200 rpm and stirring was continued for 2 hours to ensure the uniformity of the reaction and to help the coupling agent to be evenly distributed on the surface of the inorganic material to promote the reaction while avoiding excessively high temperatures that may cause side reactions of the coupling agent.
[0032] Preferably, after stirring is completed, unreacted substances or large particle impurities can be removed by filtering to ensure the purity and uniformity of the modified suspension. The filtered modified suspension can be further processed as needed, such as ultrasonic dispersion or stirring again to ensure that the particles are completely and evenly dispersed.
[0033] Preferably, the preparation of the modified suspension further comprises adding 0.1% of a dispersant, and the dispersant comprises: polyvinyl pyrrolidone (PVP).
[0034] Furthermore, the preparation of the modified suspension is carried out in a nitrogen protection environment, that is, nitrogen is added to the reaction container to prevent moisture or oxygen in the air from interfering with the hydrolysis reaction of the coupling agent, thereby ensuring the smooth progress of the reaction. By controlling the reaction environment, the occurrence of side reactions is avoided, thereby ensuring the stability and efficiency of the modified inorganic substance.
[0035] S2: melt blending LDPE, HPCTP and PBPP at a preset temperature to form a uniform inner layer matrix; LDPE (low-density polyethylene) is used as the matrix material, and HPCTP (hexaphenoxycyclotriphosphazene) and PBPP (phenoxypolyphosphazene) powders are evenly mixed as flame retardants. LDPE, HPCTP and PBPP are fully melt-blended to form a flame-retardant matrix with uniform distribution of each component, and finally extruded to form an inner layer matrix.
[0036] S3: uniformly dispersing the modified inorganic substance on the surface of the inner layer material through a coating process to form a barrier protective layer to obtain a composite matrix; The modified inorganic material is dispersed in a mixed solution of ethanol and water (the volume ratio of ethanol to water is 8:2), 2% to 5% of polyvinyl alcohol (PVA) is added as a binder, and stirred to form a coating liquid.
[0037] The coating liquid is evenly coated on the surface of the inner layer substrate particles by electrostatic spraying or dipping, and the spraying thickness is controlled to be 10-20μm. After coating, it is dried at 80°C for 3 hours to form a stable barrier protective layer. The interfacial bonding force and heat resistance of the flame retardant material are improved; the barrier protective layer can form a dense carbonized layer at high temperature to inhibit the spread of flames.
[0038] S4: mixing the composite matrix with DCP and TAIC, cross-linking and extruding at high temperature to form a composite flame retardant material; DCP (diisopropylbenzene peroxide) decomposes at high temperature to produce free radicals, which promotes the cross-linking of LDPE. TAIC (triallyl isocyanurate) acts as a co-cross-linking agent, which synergizes with DCP to improve the cross-linking efficiency.
[0039] The composite matrix, DCP (1.5%) and TAIC (0.3%) are mixed evenly in proportion and mixed and cross-linked at high temperature in a twin-screw extruder to form a composite flame retardant material after extrusion. Through the high-temperature cross-linking reaction of LDPE, a three-dimensional network structure is formed to improve the thermal stability and mechanical properties of the material.
[0040] S5: Extruding the composite flame-retardant material and cooling it to form it, and then heat-treating the extruded material to obtain a composite flame-retardant cable material.
[0041] After the composite flame retardant material is extruded by the screw, the composite flame retardant material is cooled to a certain extent and then heat-treated to further remove moisture and volatile gases in the composite flame retardant material. At the same time, the LDPE is controlled to be further cross-linked during the heat treatment process.
[0042] In step S4, when high-temperature extrusion and cross-linking reactions occur, the inorganic material coating layer will not be completely mixed with LDPE, HPCTP and PBPP, and a stable physical barrier layer will be formed on the surface of the inner layer matrix to prevent the migration of HPCTP. Inorganic materials (such as expanded graphite, montmorillonite and magnesium hydroxide) are insoluble in the polymer matrix and remain stable at high temperatures, so they can isolate the inner and outer layer materials and prevent the precipitation of HPCTP; at the same time, the protective layer formed by the inorganic material not only has a thermal isolation effect, but also helps to reduce the migration of HPCTP in the outer layer, reduce its contact with the external environment, and further reduce the risk of precipitation.
[0043] DCP decomposes at high temperatures to produce free radicals, which attack the molecular chains of LDPE and trigger cross-linking reactions. DCP comes into contact with LDPE during the extrusion process, and the free radicals produced by the decomposition can break the LDPE chain segments and cross-link them with the surrounding molecules to form a three-dimensional cross-linked network.
[0044] As a cross-linking agent, TAIC further promotes the cross-linking reaction through its olefin group and free radical reaction. It can not only enhance the uniformity of cross-linking, but also improve the degree of cross-linking, avoiding the cross-linking reaction being too fast or too slow, resulting in uneven performance of the material. TAIC helps the LDPE molecular chain to cross-link to form a more stable network structure, which not only increases the mechanical strength and thermal stability of the material, but also prevents the migration of HPCTP, because the cross-linked LDPE structure is denser, reducing the free volume and limiting the mobility of the flame retardant.
[0045] By combining the isolation and protection of the inorganic materials (expanded graphite, montmorillonite, magnesium hydroxide) in the outer layer with the cross-linking reaction of the inner layer matrix, it is possible to optimize the cross-linking structure of LDPE, HPCTP and PBPP while ensuring that HPCTP does not precipitate at high temperatures, thereby improving the thermal stability, flame retardancy and long-term weather resistance of the materials. This technical solution effectively solves the problems of HPCTP migration and uneven cross-linking at high temperatures through the synergistic effect of cross-linking and inorganic material barriers, and improves the overall performance of cable materials.
[0046] In this embodiment, an inorganic material is used to form a barrier protective film on the surface of the inner layer matrix produced by melt blending LDPE, HPCTP and PBPP to form a composite matrix, and then DCP and TAIC are used to promote the cross-linking of LDPE at high temperature and then extrude it. The extruded composite flame-retardant material is heat-treated to obtain a composite flame-retardant cable material. During the heat treatment, the LDPE is controlled to further cross-link, the cross-linking degree of the material is increased, the three-dimensional network structure is optimized, and the flame retardancy and mechanical properties of the cable material are improved.
[0047] The surface of the inorganic material is modified by a silane coupling agent, which enhances the compatibility of the inorganic material with the matrix material and improves the interfacial bonding force of the barrier protective layer. Before cross-linking, LDPE, HPCTP and PBPP are melt-blended to make each component evenly dispersed, avoid local enrichment, and improve the flame retardant uniformity of the material. The inorganic material is coated on the inner layer matrix to form a complete barrier protective layer, which effectively prevents the migration of HPCTP under high temperature conditions and improves the long-term flame retardant performance of the material. DCP and TAIC are used to ensure uniform cross-linking reaction and improve the cross-linking degree of the composite material. At the same time, under the cross-linking reaction conditions, it can ensure that the inorganic material will not melt and its performance will not be affected, maintain the integrity and interlayer structure of the inner and outer layer materials, and avoid interface damage or performance degradation during high-temperature extrusion. Finally, the extruded composite flame retardant material is heat-treated to further activate the residual cross-linking reaction, form a stable three-dimensional cross-linking structure, and improve the flame retardant performance and thermal stability of the material. At the same time, the heat treatment releases the residual stress inside the composite flame retardant material, improves the dimensional stability and long-term weather resistance, and extends the service life of the cable.
[0048] In one embodiment, the step S2: melt blending LDPE, HPCTP and PBPP at a preset temperature to form a uniform inner layer matrix; comprises: S21: dry-mix 15% to 25% HPCTP and 5% to 10% PBPP powder to obtain a uniformly distributed flame retardant powder; Pre-weigh according to the proportion of LDPE: 60%-70%, HPCTP: 15%-25%, PBPP: 5%-10%, among which LDPE is added in the form of particles to ensure that the particle diameter is uniform (about 2-5mm), and HPCTP and PBPP are added in the form of powder with a particle size controlled below 20μm.
[0049] Preferably, 15% to 25% HPCTP and 5% to 10% PBPP powders are dry mixed in a drum mixer for 5 minutes to obtain a flame retardant powder in which HPCTP and PBPP are evenly distributed, thereby reducing the risk of agglomeration between the components and facilitating the uniformity of subsequent melt blending.
[0050] S22: adding 60% to 70% LDPE into the extruder, and controlling the LDPE particles to melt into a viscous state according to preset conditions; According to the preset temperature, the low temperature zone in the twin-screw extruder is set to 90°C~100°C, and the LDPE particles are first added to the barrel and plasticized in the low temperature zone. The screw speed is set to 60rpm for 2 minutes to gradually melt the LDPE into a viscous state. The initial melting low temperature treatment can ensure that the LDPE particles are evenly melted to form a viscous matrix, creating conditions for the subsequent addition of flame retardants, while avoiding excessive temperature causing early thermal decomposition of flame retardants or degradation of the matrix.
[0051] S23: adjusting the temperature in the extruder, and adding the flame retardant powder into the extruder in multiple times to obtain a mixture; After LDPE is completely melted (about 100°C), the premixed HPCTP and PBPP powders are quantitatively added into the extruder multiple times.
[0052] Preferably, HPCTP and PBPP powders are added to the extruder in three times, 40% of the total amount is added in the first time, 40% of the total amount is added in the second time, and the remaining 20% is added in the third time. The staged feeding time is controlled to be 2 minutes each time, during which the screw speed is maintained at 50-60 rpm, and the barrel temperature is simultaneously increased to 130°C.
[0053] By adding the flame retardant in stages, excessive instantaneous contact between the flame retardant and LDPE can be avoided, the risk of uneven dispersion can be reduced, and the flame retardant can be gradually dispersed into the molten matrix, ultimately forming a uniform inner layer matrix material.
[0054] S24: adjusting the speed and maintaining the temperature, performing high shear mixing on the mixture, and completing high shear mixing extrusion to obtain an inner layer matrix; The screw speed was increased to 80 rpm, while the barrel temperature was maintained at 130°C, and the mixture in the extruder was subjected to high shear mixing for 5 minutes. At the same time, a dispersion disc structure was added to the extruder to further refine the flame retardant particles through high shear force and evenly distribute them in the matrix.
[0055] High shear dispersion allows HPCTP and PBPP powders to be evenly embedded in the LDPE matrix, while forming a tight molecular mosaic structure to ensure the uniformity of the inner matrix and avoid local aggregation that affects performance. Through the combined action of high shear dispersion and dispersion disk, the microscopic distribution of the flame retardant is strengthened and the stability of the material is improved.
[0056] After the mixing is completed, the volatile impurities and possible moisture are discharged through the exhaust holes of the twin-screw extruder, the extrusion temperature is maintained at 130°C, the screw speed is adjusted to 40rpm, and the initial discharge is completed under low speed conditions. The initial extruded material is in granular form and is collected after cooling for later use.
[0057] The initially discharged granular material is sieved (sieve hole diameter 1mm) to remove large particles or unmixed parts; the sieved particles are placed in a vacuum drying oven and dried at 80°C for 4 hours to ensure complete dehydration; the dried particles are sealed and stored in a dry environment (relative humidity <10%).
[0058] In one embodiment, the S3: uniformly dispersing the modified inorganic substance on the surface of the inner layer material by coating to form a barrier protective layer to obtain a composite matrix includes: S31: using an electrostatic spraying method or a dipping method, the modified suspension is evenly covered on the surface of the inner layer substrate to form the barrier protection layer, thereby obtaining a composite substrate.
[0059] When using an electrostatic spraying device for electrostatic spraying, calibrate the airflow of the equipment before spraying to ensure uniform spraying (spraying pressure 2-4MPa). Spread the inner layer substrate flat on the rotary coating platform, adjust the platform speed, and keep the spraying distance at about 15cm. Repeat the spraying multiple times with a spraying amount of 50-80μL each time to ensure that the thickness of the coating layer is within the range of 10-20μm. After the coating is completed, let the material stand for 15 minutes to initially form surface adhesion.
[0060] When the modified inorganic substance is uniformly coated on the surface of the inner layer material to form a barrier protective layer by immersion method, the inner layer substrate is immersed in the modified suspension for 2 to 5 minutes to ensure uniform wetting of the surface of the inner layer material. During the immersion process, ensure that the inner layer substrate is completely immersed in the suspension and that the modified inorganic substance is uniformly covered on its surface.
[0061] When the composite matrix needs to be stored for a long time, step S3 further includes: S32: placing the coated composite substrate in a hot air circulation drying oven, controlling the temperature at 50-60°C, and drying for 30-60 minutes; turning the material every 10 minutes during the drying process to prevent adhesion between particles or uneven coating.
[0062] S33: The coated granular material is sieved through a 2 mm sieve to remove possible agglomerates.
[0063] The screened materials are packed into dry sealed bags and stored in an environment with a humidity below 10% and a temperature below 25°C.
[0064] In one embodiment, when the modified suspension needs to be stored for a long time, S2 further includes S14: vacuum filtering, separating, washing, and drying the modified suspension to obtain the modified inorganic substance; The S3 further includes S30: preparing an ethanol-water mixed solution to obtain the modified inorganic substance, and slowly adding the modified inorganic substance into the ethanol-water mixed solution to obtain the modified suspension.
[0065] Specifically, after the reaction is completed, the modified inorganic substance is separated by vacuum filtration, and the filter cake is obtained and washed with anhydrous ethanol for 3 to 4 times to remove unreacted coupling agent and by-products; finally, it is rinsed once with pure water to ensure that there are no impurities remaining on the surface of the inorganic substance, so as to achieve the preparation of high-purity modified inorganic substances and avoid impurities affecting the interface bonding performance.
[0066] The washed modified inorganic material was placed in a vacuum drying oven, set at 80°C, controlled at 50 kPa, and dried for 8 hours. During the drying process, the modified inorganic material was gently turned over every 2 hours to prevent it from agglomerating. The dried modified inorganic material was sieved through a fine sieve (pore size 150 μm) to remove large particles or agglomerates.
[0067] An ethanol-water mixed solution is prepared, wherein the volume ratio of ethanol to water is 9:1 to 8:2; 5% to 10% of the modified inorganic substance by mass of the inorganic substance is obtained, and the modified inorganic substance is slowly added into the ethanol-water mixed solution to obtain a coating medium; Before adding the modified inorganic substance into the ethanol-water mixed solution, the modified inorganic substance was placed in a vacuum drying oven with the temperature set at 80° C. and the drying time set at 2 hours to completely remove residual moisture and solvent.
[0068] The modified inorganic substance was slowly added to the ethanol-water mixed solution, while stirring and ultrasonically treating for 10 minutes (frequency 25 kHz, power 300 W) to form a uniform suspension.
[0069] Preferably, a proper amount of binder (such as polyvinyl alcohol, PVA) is added to the suspension at a ratio of 2% to 5%, and stirring is continued for 15 minutes to ensure that the viscosity of the solution is stable (viscosity range: 800 to 1200 mPa·s). The addition of the binder also enhances the adhesion between the suspension and the inner layer substrate, and can form a uniform barrier protective layer on the surface of the inner layer substrate.
[0070] Furthermore, before S31, the process further includes: slicing the inner layer substrate, wiping and cleaning with ethanol to remove surface impurities and oil stains, and then slightly roughening the surface with sandpaper to form a microscopic rough structure to improve the adhesion of the coating layer. After roughening, the surface of the inner layer substrate is cleaned of residual dust using a high-pressure airflow and wiped with ethanol to ensure a clean surface.
[0071] In one embodiment, the step S4: mixing the composite matrix with DCP and TAIC, and subjecting the composite matrix to high temperature extrusion and cross-linking reaction at 170° C. to 190° C. to form a composite flame retardant material comprises: S41: obtaining DCP (crosslinking agent diisopropylbenzene peroxide) and TAIC (triallyl isocyanurate), dissolving DCP and TAIC in a small amount of anhydrous ethanol, and stirring to form a uniform crosslinking spray liquid; Further, 1.2% to 2% of DCP and 0.3% to 0.5% of TAIC are dissolved in a small amount of anhydrous ethanol and stirred to form a uniform cross-linking spray liquid.
[0072] Further, DCP and TAIC were dissolved in a small amount of anhydrous ethanol at a mass ratio of 3:1 to 5:1, and the amount of DCP and TAIC was obtained according to 2% to 3% of the composite matrix.
[0073] DCP and TAIC were dissolved in a small amount of anhydrous ethanol at 30°C and stirred for 10 min to form a uniform cross-linking spray solution.
[0074] S42: spraying the cross-linking spray liquid uniformly onto the composite matrix through a spraying device, and controlling the composite matrix to mix and rotate; In a low-speed rotating mixing device, the cross-linking spray liquid is evenly sprayed onto the surface of the composite matrix particles through a spray device, and the roller is mixed while spraying to ensure that the cross-linking agent is evenly attached to the composite matrix particles. The mixing is continued for 3 to 5 minutes to ensure that DCP and TAIC are fully in contact with the composite matrix.
[0075] S43: drying the composite matrix, DCP and TAIC that have been mixed together, and adding the dried mixed material into a twin-screw extruder; Place the mixed material in a vacuum drying oven, set the temperature to 80°C ~ 90°C, maintain the vacuum degree at 50 ~ 70kPa, and control the drying time to 2 ~ 3 hours to ensure that the moisture content of the material drops below 0.1%.
[0076] S44: performing segmented processing on the mixture entering the twin-screw extruder to complete crosslinking and then extrude to obtain a molten material, wherein the segmented processing sequentially includes: feeding processing, melting processing, mixing processing, and discharging processing; The barrel is divided into sections, which are: The feeding zone is used for feeding processing. The temperature is set at 150°C to partially soften the mixture and enhance its fluidity, ensuring that the mixture can smoothly enter the extruder; The melting zone is used for melting treatment. The temperature is set at 170 degrees and the screw speed is set at 60 rpm, so that LDPE, HPCTP, PBPP, DCP, and TAIC are completely melted, plasticized, and mixed together to provide conditions for subsequent cross-linking; The mixing zone is used for mixing treatment. The temperature is set at 180°C~190°C, and the screw speed is increased to 60~80rpm. Under the conditions of screw shear force and high temperature, DCP is activated to decompose and generate free radicals to complete the initial cross-linking reaction; The discharging area is used for discharging processing. The die temperature is controlled at 180°C, and the material after the cross-linking reaction is extruded through the die.
[0077] S45: Cooling the extruded molten material and placing it in a hot air circulation for fixing treatment, and obtaining the composite flame retardant material after the fixing treatment is completed.
[0078] The extruded material is rapidly cooled through a water cooling tank (temperature 25°C) and collected into a sheet or granular composite material. After cooling, the sheet or granular composite material is placed in a hot air circulation furnace (80°C, 2 hours) for post-curing treatment to further stabilize the cross-linking structure, and a composite flame retardant material is obtained after curing.
[0079] In one embodiment, the step S5: extruding the composite flame retardant material and cooling it to form it, and then heat treating the extruded material to obtain the composite flame retardant cable material, comprises: S51: Cooling the composite flame retardant material by combining water cooling and air cooling, and screening qualified composite flame retardant materials; The temperature of the water bath cooling system is set to 15°C ~ 25°C, and the composite flame retardant material just extruded from the die mouth is sent into the water bath cooling system for the first cooling. After staying for 1~2 minutes, the composite flame retardant material is continued to be sent to the air cooling channel for the second cooling. The air flow rate is controlled at 5~10m / s, and the duration is 30~60 seconds.
[0080] The newly extruded composite flame retardant material is quickly cooled and initially formed through water cooling and air cooling to ensure that the extruded composite flame retardant material maintains a stable shape while avoiding internal stress accumulation or appearance defects due to excessive cooling, providing high-quality semi-finished products for subsequent heat treatment.
[0081] During the cooling process, monitor whether the composite flame retardant material has cracks, bubbles, etc., pick out unqualified products, and screen out qualified composite flame retardant materials for the next step.
[0082] S52: performing hot air drying on the composite flame retardant material, first adjusting the temperature step by step to increase the activation of the cross-linking reaction; S53: Cooling the composite flame-retardant material that has undergone cross-linking reaction again to obtain the composite flame-retardant cable material.
[0083] The cooled composite flame retardant material is placed in a hot air circulation drying system. In the first stage, the temperature is raised from 50°C to 150°C, and the heating rate is controlled to be 5°C / min. The material is heated gradually to avoid stress concentration in the material due to excessive temperature difference. In the second stage, the temperature is controlled at 195°C~205°C, and the composite flame retardant material is kept at a constant temperature for 8~10 minutes to stimulate the cross-linking reaction, activate the residual cross-linking reaction, and increase the degree of cross-linking. In the third stage, the material is cooled gradually at a cooling rate of 10°C / min to prevent cracks in the material due to sudden cooling, and the composite flame retardant cable material is obtained after cooling.
[0084] Through heat treatment, the incompletely decomposed DCP is further activated to generate more free radicals, complete the residual cross-linking reaction, and increase the cross-linking degree of the material to 90% to 95%, forming a stable three-dimensional network structure; stress release is achieved during the heating and cooling process to avoid cracks in the composite flame-retardant cable material, which may affect the quality of the cable material.
[0085] In one embodiment, cooling the composite flame retardant material by a combination of water cooling and air cooling and after screening qualified composite flame retardant materials, further comprises: uniformly dispersing the modified suspension on the surface of the composite flame retardant material by coating to form a protective layer.
[0086] In the composite flame retardant material extruded through step S4, the inorganic material will be partially mixed in the interior of the mixture of LDPE, HPCTP and PBPP, and the HPCTP will be located on the surface of the material. In order to meet higher usage requirements or when the cable material will be in a high temperature environment, after the composite flame retardant material is extruded, the modified suspension obtained in steps S11 to S13 is coated on the surface of the composite flame retardant material by immersion or electrostatic spraying to form a protective layer, which is used to prevent the HPCTP from precipitating when the composite flame retardant material is in a high temperature state during heat treatment or in subsequent processes, thereby affecting the quality of the composite flame retardant cable material and its service life.
[0087] Example 2 Based on the preparation method of the composite flame-retardant cable material described in the above embodiment 1, the raw material ratio of the composite flame-retardant cable material is: Low-density polyethylene (LDPE): 60% to 70%; Hexaphenoxycyclotriphosphazene (HPCTP): 15% to 25%; Phenoxypolyphosphazene (PBPP): 5% to 10%; Dicumyl peroxide (DCP): 1.2% to 2%; Triallyl isocyanurate (TAIC): 0.3% to 0.5%; Modified suspension; The modified suspension comprises: Inorganic materials: 8% to 12%, wherein the inorganic materials include: one or more of expanded graphite, montmorillonite, and magnesium hydroxide; Ethanol: 60%-70%; Water: 10%-20%; Silane coupling agent: 5%~8%; Glacial acetic acid: trace amount (about 0.5%).
[0088] The inner layer matrix is formed by melt blending 60% to 70% LDPE, 15% to 25% HPCTP, and 5% to 10% PBPP by the method described in step S2, wherein LDPE is the main raw material, and HPCTP and PBPP are flame retardants.
[0089] The inorganic material is modified by a silane coupling agent to generate a modified suspension, and a barrier protective layer is generated outside the inner layer substrate by a multiple coating method to obtain a composite substrate. The isolation protective layer can prevent the HPCTP in the inner layer substrate from precipitating in the subsequent high-temperature cross-linking reaction and the subsequent cable material during use, affecting the quality of the cable material or shortening its service life.
[0090] The cross-linking agents (DCP and TAIC) promote the cross-linking structure of LDPE through step S4, improve the thermal stability and mechanical strength of the cable material, and ensure the performance of the cable under high temperature and external environment.
[0091] When preparing the modified suspension, a chemical bonding layer is formed between the coupling agent and the inorganic surface to enhance the stability and adhesion of the barrier protective layer. The modified suspension ensures the high performance of the final cable material through precise component ratio and process control, including excellent flame retardancy, thermal stability, mechanical properties and excellent processability.
[0092] In one embodiment, the modified suspension is prepared using three inorganic materials, namely expanded graphite, montmorillonite and magnesium hydroxide, and the mass ratio of expanded graphite, montmorillonite and magnesium hydroxide is 4:3:3.
[0093] Furthermore, the preparation of the modified suspension also includes adding 0.1% of a dispersant and stirring evenly, and the dispersant includes: polyvinyl pyrrolidone (PVP).
[0094] In one embodiment, the raw material ratio of the composite flame-retardant cable material is: Low-density polyethylene (LDPE): 60%; Hexaphenoxycyclotriphosphazene (HPCTP): 20%; Phenoxypolyphosphazene (PBPP): 10%; Dicumyl peroxide (DCP): 1.5%; Triallyl isocyanurate (TAIC): 0.3%; Modified suspension; The modified suspension comprises: expanded graphite: 8%; ethanol: 65%; water: 10%; silane coupling agent: 6%; and glacial acetic acid: a trace amount (about 0.5%).
[0095] According to the above ratio and in accordance with the preparation scheme provided in Example 1, a composite flame-retardant cable material is prepared.
[0096] In one embodiment, the raw material ratio of the composite flame-retardant cable material is: Low-density polyethylene (LDPE): 65%; Hexaphenoxycyclotriphosphazene (HPCTP): 15%; Phenoxypolyphosphazene (PBPP): 10%; Dicumyl peroxide (DCP): 1.3%; Triallyl isocyanurate (TAIC): 0.4%; Modified suspension; The modified suspension comprises: magnesium hydroxide: 8%, ethanol: 65%, water: 15%, silane coupling agent: 5%, and glacial acetic acid: trace amount (about 0.5%).
[0097] According to the above ratio and in accordance with the preparation scheme provided in Example 1, a composite flame-retardant cable material is prepared.
[0098] As described above, the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a composite flame-retardant cable material, characterized in that: The preparation method comprises: S1: obtaining a modified suspension according to an inorganic material and a silane coupling agent, wherein the inorganic material comprises one or more of expanded graphite, montmorillonite, and magnesium hydroxide; S2: at a preset temperature, LDPE, HPCTP and PBPP are melt-blended to form a uniformly dispersed inner layer matrix; S3: uniformly dispersing the modified suspension on the surface of the inner layer substrate by coating to form a barrier protective layer to obtain a composite substrate; S4: mixing the composite matrix with DCP and TAIC, cross-linking and extruding at high temperature to form a composite flame retardant material; S5: Extruding the composite flame-retardant material and cooling it to form it, and then heat-treating the extruded material to obtain a composite flame-retardant cable material.
2. The method for preparing a composite flame-retardant cable material according to claim 1, characterized in that: The modified suspension is obtained according to the inorganic material and the silane coupling agent, wherein the inorganic material includes one or more of expanded graphite, montmorillonite, and magnesium hydroxide, including: S11: adding the inorganic material into the anhydrous ethanol solution at a mass ratio of 1:10 and stirring and dispersing the inorganic material; during the dispersing process, ultrasonic vibration is used to assist the dispersion to obtain an inorganic suspension; S12: weighing a silane coupling agent according to 5% to 8% of the mass of the inorganic material and preparing an activation solution, adjusting the pH value of the activation solution, and stirring to obtain an activated coupling agent solution; S13: slowly adding the modified suspension into the activated coupling agent solution, and continuously stirring for 2 hours to obtain a modified suspension, wherein the suspended matter in the modified suspension is a modified inorganic substance.
3. The method for preparing a composite flame-retardant cable material according to claim 2, characterized in that: The method comprises: melt-blending LDPE, HPCTP and PBPP at a preset temperature to form a uniformly dispersed inner layer matrix, comprising: S21: dry-mix 15% to 25% HPCTP and 5% to 10% PBPP powder to obtain a uniformly distributed flame retardant powder; S22: adding 60% to 70% LDPE into the extruder, and controlling the LDPE particles to melt into a viscous state according to preset conditions; S23: adjusting the temperature in the extruder, and adding the flame retardant powder into the extruder in multiple times; S24: Adjust the speed and maintain the temperature, perform high shear mixing on the mixture, and then extrude the inner layer matrix.
4. The method for preparing a composite flame-retardant cable material according to claim 3, characterized in that: When the modified inorganic substance needs to be stored for a long time, S2 further includes S14: vacuum filtering, separating, washing, and drying the modified suspension to obtain the modified inorganic substance; The S3 includes S30: preparing an ethanol-water mixed solution to obtain the modified inorganic substance, and slowly adding the modified inorganic substance into the ethanol-water mixed solution to obtain the modified suspension.
5. The method for preparing a composite flame-retardant cable material according to claim 4, characterized in that: The modified inorganic substance accounts for 8% to 12% of the composite matrix.
6. The method for preparing a composite flame-retardant cable material according to claim 5, characterized in that: The composite matrix is mixed with DCP and TAIC, and subjected to high temperature extrusion and cross-linking reaction at 170° C. to 190° C. to form a composite flame retardant material, comprising: S41: obtaining DCP and TAIC, dissolving the DCP and TAIC in a small amount of anhydrous ethanol, and stirring to form a uniform cross-linking spray liquid; S42: spraying the cross-linking spray liquid uniformly onto the composite matrix through a spraying device, and controlling the composite matrix to mix and rotate; S43: drying the composite matrix, DCP and TAIC that have been mixed together, and adding the dried mixture into a twin-screw extruder; S44: performing segmented processing on the mixture entering the twin-screw extruder to complete crosslinking and then extrude to obtain a molten material, wherein the segmented processing sequentially includes: feeding processing, melting processing, mixing processing, and homogenizing processing; S45: Extruding the molten material to obtain a composite flame retardant material.
7. The method for preparing a composite flame-retardant cable material according to claim 6, characterized in that: The method of extruding the composite flame retardant material and cooling it to form it, and then heat treating the extruded material to obtain the composite flame retardant cable material comprises: S51: Cooling the composite flame retardant material by combining water cooling and air cooling, and screening qualified composite flame retardant materials; S52: performing hot air drying on the composite flame retardant material, first adjusting the temperature step by step to increase the activation of the cross-linking reaction; S53: Cooling the composite flame-retardant material that has undergone cross-linking reaction again to obtain the composite flame-retardant cable material.
8. The method for preparing a composite flame-retardant cable material according to claim 7, characterized in that: The method further comprises: cooling the composite flame retardant material by combining water cooling and air cooling, and after screening the qualified composite flame retardant material, uniformly dispersing the modified suspension on the surface of the composite flame retardant material by coating to form a protective layer.
9. A composite flame-retardant cable material, characterized in that: The composite flame-retardant cable material is made according to the preparation method of claim 1 or 8, and the ratio of raw materials of the composite flame-retardant cable material includes: Low-density polyethylene (LDPE): 60% to 70%; Hexaphenoxycyclotriphosphazene (HPCTP): 15% to 25%; Phenoxypolyphosphazene (PBPP): 5% to 10%; Dicumyl peroxide (DCP): 1.2% to 2%; Triallyl isocyanurate (TAIC): 0.3% to 0.5%; Modified suspension; The modified suspension comprises: Inorganic materials: 8% to 12%, wherein the inorganic materials include: one or more of expanded graphite, montmorillonite, and magnesium hydroxide; Ethanol: 60%-70%; Water: 10%-20%; Silane coupling agent: 5%~8%; Glacial acetic acid: trace amount (about 0.5%).
10. The composite flame-retardant cable material according to claim 9, characterized in that: The inorganic material comprises expanded graphite, montmorillonite and magnesium hydroxide, and the mass ratio thereof is 4:3:3.
Citation Information
Patent Citations
Flame-retardant cross linked polyethylene insulation power cable
CN103928172A
Epoxy resin flame-retardation composition and preparation method thereof
CN106243630A
Halogen-free flame retardant outer insulating material for cables in nuclear island, outer insulating layer for cables and preparation method of insulating material
CN109438813A
High-temperature-resistant flame-retardant polyethylene cable material and preparation method thereof
CN117659540A
High-temperature-resistant flame-retardant polyethylene cable material and preparation method thereof
CN117700862A
Cited By
Corrosion-resistant alkali-resistant marine water-blocking cable and preparation method thereof
CN121034770A